The elderly : contemporary issues - Sattar, M. A.; Kabir, M.; Bangladesh Association of Gerontology (Dhaka : Bangladesh Association of Gerontology, 2003)
Contributed articles, with reference to Bangladesh.
Includes bibliographical references and index.
Some articles in Bengali.
Keywords: Older people -- Bangladesh -- Social conditions